اقتراح خوارزمية لاستخلاص قيمة العداد الصناعي من صور مخططاتها النبضية - علي سليمان; بلال شيحا; محمد كفرناوي (Tishreen University, 2017)
يقدم هذا البحث خوارزمية من أجل استخلاص القيمة العددية من صورة المخططات النبضية للعدادات الصناعية، وذلك بمعالجة صورة المخطط النبضي للعداد بعد إجراء عملية تقسيم وتجزئة للمخطط النبضي، وتحديد لحظات التغير ونوعها فيما لو كانت جبهة صاعدة ذات قيمة 1)) أم جبهة هابطة ذات قيمة (0)، ومن ثم حساب عدد الجبهات الكلية سواء كانت جبهات صاعدة أو هابطة، ومعرفة القيمة العددية للعداد الصناعي من خلال قسمة عدد الجبهات على (2)، وقد تم معالجة نوعين من المخططات النبضية، النوع الأول مخططات نبضية ذات إشارات نبضية مفرغة (البكسلات التي تحتويها النبضة ذات لون أبيض) والنوع الثاني مخططات نبضية ذات إشارات نبضية ممتلئة (البكسلات التي تحتويها النبضة ذات لون مغاير للأبيض)، وقد طُورت الخوارزمية المقترحة لتشمل النوعين، وصُممت واجهة برمجية لهذه الخوارزمية باستخدام برنامج ماتلاب، وقد تم تجربتها على ثلاث صور مخططات نبضية، فأعطت نتائج دقيقة باستخلاص القيمة العددية للعداد الصناعي سواء للمخططات ذات النبضات المفرغة أو الممتلئة وكانت نسبة الدقة100% من أجل المخططات المدروسة، وذلك بسبب توصل لنسبة تعرف وتمييز100%بالنسبة للشبكة العصبونية المستخدمة وتمكن الخوارزمية المقترحة لمعرفة عدد الجبهات من معرفة عدد الجبهات بنسبة100%. This paper introduces an algorithm to find out value of number for industrial counter from image of pulse plan. that is achieved by image processing of pulse plan for counter, pulse plan has been segmentation, and alternating times and type are detected. Type of alternating time means that if they are rising edge, that has zero value, or if they are falling edge, that has one value. Number of total edge is calculated for both type rising or falling. Number of value for counter is calculated by dividing number of edges on two. Two type of pulse plans are processed, the first one is pulse plans have empty pulse signals (pulse contains white pixels) and the second one is pulse plans have filled pulse signals (pulse contains nonwhite pixels). Proposal algorithm is developed to process two types. Programming interface is designed using MatLab for proposal algorithm. Three image of pulse plans are applied on this programming interface. It gives perfect results, by rate 100% and value of number for industrial counter is extracted for plans contains empty pulse or filled one. Rate of That is because used neoural neworked has 100% recogition rate, and proposal algorithm can find number of edges by 100% rate.